Resposta :
Resposta:
Solução:
[tex]\sf \displaystyle Dados: \begin{cases} \sf f(x) = 3x + 8 \\ \sf g(x) = f(x) - 9 \\ \sf g(4) = \:? \end{cases}[/tex]
[tex]\sf \displaystyle g(x) = f(x) -9[/tex]
[tex]\sf \displaystyle g(x) = (3x+8) -9[/tex]
[tex]\sf \displaystyle g(x) = 3x+8 -9[/tex]
[tex]\sf \displaystyle g(x) = 3x-\:1[/tex]
[tex]\sf \displaystyle g(4) = 3\cdot 4-\:1[/tex]
[tex]\sf \displaystyle g(4) = 12-\:1[/tex]
[tex]\boxed{ \boxed { \boldsymbol{ \sf \displaystyle g(4) = 11 }}} \quad \gets \mathbf{ Resposta }[/tex]
Explicação passo-a-passo: